Reply to "Comment on "An improved quantum-behaved particle swarm optimization method for short-term combined economic emission hydrothermal scheduling" by Songfeng Lu, et al. [Energy Convers. Manage. 51 (2010) 561–571]". (15th May 2015) - Sun, Chengfu; Lu, Songfeng
Abstract: Comments were made by Ali Esmaeel Nezhad and Abdollah Ahmadi on a publication by S. Lu, et al. on hydrothermal scheduling. In real world, the hydro schedule in [Energy Convers. Manage. 51 (2010) 561–571] is also a possible solution. But the power produced by some hydro unit may not reflect the real world value. The mathematic model should be amended to obey real hydrothermal schedule.